High frequency inverter topologies integrated with the coupled inductor bridge arm. Issue 6 (1st May 2016) - Hu, Yihua; Ji, Bing; Finney, Stephen; Xiao, Weidong; Cao, Wengping
Abstract : A new topology of the high frequency alternating current (HFAC) inverter bridge arm is proposed which comprises a coupled inductor, a switching device and an active clamp circuit. Based on it, new single‐phase and three‐phase inverters are proposed and their operating states are analysed along with the traditional H‐bridge inverter. Multi‐phase and multi‐level isolated inverters are also developed using the HFAC bridge arm. Furthermore, based on the proposed HFAC, a front‐end DC–DC converter is also developed for photovoltaic systems to demonstrate the application of the proposed HFAC converter. Simulation and experimental results from prototype converters are carried out to validate the proposed topologies which can be utilised widely in high frequency power conversion applications such as induction heating and wireless power transfer.